(untitled) (E Conference Zone, 2022)
The article discusses the concept of “smart technology”. The substantiation of the significant impact of the development of information technology on the requirements for the content and quality of education in universities is presented. It reveals the role of universities in bringing new knowledge and methods to the development of the economy and society